Dual sources of melatonin and evidence for different primary functions - Reiter, Russel J.; Sharma, Ramaswamy; Tan, Dun-Xian; Chuffa, Luiz Gustavo de Almieda; da Silva, Danilo Grunig Humberto; Slominski, Andrzej T.; Steinbrink, Kerstin; Kleszczynski, Konrad (Frontiers in Endocrinology, 2024)
This article discusses data showing that mammals, including humans, have two sources of melatonin that exhibit different functions. The best-known source of melatonin, herein referred to as Source #1, is the pineal gland. In this organ, melatonin production is circadian with maximal synthesis and release into the blood and cerebrospinal fluid occurring during the night. Of the total amount of melatonin produced in mammals, we speculate that less than 5% is synthesized by the pineal gland. The melatonin rhythm has the primary function of influencing the circadian clock at the level of the suprachiasmatic nucleus (the CSF melatonin) and the clockwork in all peripheral organs (the blood melatonin) via receptor-mediated actions. A second source of melatonin (Source # 2) is from multiple tissues throughout the body, probably being synthesized in the mitochondria of these cells. This constitutes the bulk of the melatonin produced in mammals and is concerned with metabolic regulation. This review emphasizes the action of melatonin from peripheral sources in determining re-dox homeostasis, but it has other critical metabolic effects as well. Extrapineal melatonin synthesis does not exhibit a circadian rhythm and it is not released into the blood but acts locally in its cell of origin and possibly in a paracrine matter on adjacent cells. The factors that control/influence melatonin synthesis at extrapineal sites are unknown. We propose that the concentration of melatonin in these cells is determined by the subcellular redox state and that melatonin synthesis may be inducible under stressful conditions as in plant cells.